1989
DOI: 10.1242/jcs.93.4.641
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the biological activities of the cell-adhesive proteins vitronectin and fibronectin

Abstract: The effects of vitronectin and fibronectin upon the attachment and growth of bovine corneal endothelial cells (BCE) and BHK-21 cells were compared. Similar dose-response curves for cell attachment to the substratum were obtained for both molecules and both cell types, although BCE cells exhibited a slight preference for vitronectin, and BHK cells for fibronectin. When, however, cells were plated in medium containing bovine serum stripped of fibronectin, they attached and grew normally, whereas in medium contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…However, this is not surprising, as it is reported that in complex protein solutions Fn interacts with the available cell non-adhesive molecules, 53 which reduces its competitiveness and explains its failure to adsorb on to the substrate in the presence of other serum proteins. 54 As a result, in bovine plasma and fresh serum higher cell activity is associated with Vn but not with Fn.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not surprising, as it is reported that in complex protein solutions Fn interacts with the available cell non-adhesive molecules, 53 which reduces its competitiveness and explains its failure to adsorb on to the substrate in the presence of other serum proteins. 54 As a result, in bovine plasma and fresh serum higher cell activity is associated with Vn but not with Fn.…”
Section: Discussionmentioning
confidence: 99%
“…Vitronectin has been implicated in the attachment of a number of cell types, including human endothelial cells, 5 to tissue culture surfaces. This may explain to some extent, other data showing high levels of cell adhesion to acid-containing plasma deposited surfaces in preference to other plasma polymers.…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption of adhesive proteins such as fibronectin and vitronectin has been shown to be of great importance when culturing a variety of cells in vitro. [5][6][7] Plasma polymerisation is a promising route to fabrication of surfaces with diverse properties. 8 In plasma polymerisation a thin (v 100 nm) film may be deposited onto substrates of complex geometry, modifying the chemistry of the surface region.…”
Section: Introductionmentioning
confidence: 99%
“…One important reason is the increased protein adsorption on the surfaces with moderate hydrophilicity ( Lee et al, 1998 ). The improved adsorption of cell-adhesive serum proteins such as vitronectin and fibronectin can highly affect cell adhesion, growth, and morphology ( van Wachem et al, 1987 ; Underwood and Bennett, 1989 ; Steele et al, 1995 ). PCL nanofibers are inherently hydrophobic and do not expose polar functional groups on the surface.…”
Section: Reinforcing and Hydrophilizing Additivesmentioning
confidence: 99%